Patient Discomfort Experience During ETT Insertion in Intensive Care Unit Husada Hospital Jakarta, Indonesia - Ni Putu Ayu J Sastamidhyani; Ni Luh Widani; Agustinus Bandur (Babali Nursing Research, 2022)
Introduction: Organ dysfunction may lead to critical disease. The critical disease has put many patients to be monitored intensively during medical treatment to restore their body function. Most ventilator usage is to support recovery from respiratory system problems. A ventilator is connected to an Endo Tracheal Tube inserted into the patient’s mouth. This study aims to explore in depth the meaning of patient experience dealing with endotracheal tube insertion during hospitalization in intensive care unit. Methods: This study used a qualitative research design with an interpretative phenomenological approach. This study used purposive sampling, with total 10 participants with inclusion criteria: patient that has endotracheal tube experience more than 2 x 24 hours, 30-70 years of age, conscious, has good memory while in intensive care unit, able to communicate well and are willing to become participants by signing the participant’s informed consent form. The data collection strategy used in-depth interview techniques with semi-structured interview guidelines. Researchers conducted data analysis using NVivo. Results: There are five themes in this study, namely: pain, feeling thirsty, disoriented, feeling anxiety, and hard to communicate verbally. Conclusion: Discomfort experienced in patients while utilizing endotracheal tubes and ventilators affects both physically, psychologically, socially, and spiritually. It takes a lot of courage to survive during those hard times. Patients adapt by praying, showing an obedient attitude, keeping calm, and trying to find out their self-comfort position.